Mechanical properties of recycled aluminium chip reinforced with alumina (Al2O3) particle - Lajis, M. A.; Ahmad, A.; Yusuf, N.K.; Azami, A. H.; Wagiman, A. (Wiley, 2017)
Metal matrix composites spur the possibility of advancing typical monolithic materi-al properties. Offering great strength, lightweight and being able to withstand high temperatures are the main behaviours of the metal matrix composite. To that ex-tent, many practitioners in either automotive or aerospace industries employed metal matrix composite in most of the critical parts. Forming metal matrix composite via solid state processing is considered innovative, as most of the metal matrix composite forming process took place either in liquid or gaseous processing. This paper studied in varying alumina amount from 1 to 5 wt% that had been introduced to recycled aluminium chip employing hot press forging. Aluminium chip was ob-tained by milling AA6061-T6 bulk to a certain parameter. The medium size chips were cleaned, dried and mixed with alumina particles before being poured into a closed-die mould. The main responses investigated were ultimate tensile strength and elongation to failure. Out of all fractions, 2 wt% of alumina ousted the other by significantly strengthening the composite and ductility, slightly better than the stan-dard value. Further addition of alumina would enhance the composite strength, but in contrary, it also could threaten the material performance.